2015
DOI: 10.1111/jvs.12322
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐species competition experiments with peatland bryophytes

Abstract: Question Species interactions are one of the processes determining composition of plant communities. We used the community density series method to study competition in a multi‐species community of bryophytes common in calcareous fens. The succession of mires is driven by Sphagnum species, which are supposedly superior to brown mosses in competition for resources and space, but little is known about the environmental conditions in which brown mosses can prevail when subject to neighbour interactions. How are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
3
21
2
Order By: Relevance
“…Many laboratory‐ and field‐based experimental studies have inferred competition as the mechanism driving changes in the abundance or occurrence of one species as a function of the abundance or occurrence of another (Connell , Goldberg and Barton , Udd et al. ), but contrary to expectations, we found that species within a group of potential competitors were consistently aggregated (Fig. ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Many laboratory‐ and field‐based experimental studies have inferred competition as the mechanism driving changes in the abundance or occurrence of one species as a function of the abundance or occurrence of another (Connell , Goldberg and Barton , Udd et al. ), but contrary to expectations, we found that species within a group of potential competitors were consistently aggregated (Fig. ).…”
Section: Discussioncontrasting
confidence: 99%
“…Competition has often been regarded as the dominant species interaction and among the most important mechanisms driving community structure (Elton 1946, Diamond 1975, Meyer and Kalko 2008; however, this assumption has often lacked appropriate quantitative testing Simberloff 1979, Englund et al 2009). Many laboratory-and field-based experimental studies have inferred competition as the mechanism driving changes in the abundance or occurrence of one species as a function of the abundance or occurrence of another (Connell 1983, Goldberg and Barton 1992, Udd et al 2016, but contrary to expectations, we found that species within a group of potential competitors were consistently aggregated (Fig. 3) Fig.…”
Section: Species Co-occurrence Patternscontrasting
confidence: 99%
“…Similar interactions have been observed in multi‐species experiments where Sphagnum spp. were out‐competed by true mosses in wet rich fens (Udd et al., ) and A. palustre was competitively excluded in mature communities (Li & Vitt, ). In boreal rich fens, T. nitens is one of the most abundant and has the widest habitat niche breadth among true peatland moss species (Gignac, ; Vitt, Wieder, Scott, & Faller, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is mixed evidence for biotic filtering due to interspecific bryophyte competition, with studies showing that competitive exclusion may (e.g. Li & Vitt, 1995;Udd, Sundberg, & Rydin, 2016) or may not (e.g. Mälson & Rydin, 2009;Økland, 1994) affect species occurrences.…”
Section: Introductionmentioning
confidence: 99%